비육돈의 도체형질과 MYL2, ADCYAP1R1 유전자 다형성의 상관관계 - 한상현; 신광윤; 이성수; 고문석; 성필남; 권기백; 조인철; Han, ang-Hyun; Shin, Kwang-Yun; Lee, Sung-Soo; Ko, Moon-Suck; Seong, Pil-Nam; et al. (Journal of animal science and technology, 2008)
DNA variation of MYL2 intron 5 A345G and ADCYAP1R1 intron 2 A337G were investigated for carcass trait association in finished pigs. Three genotypes(two homozygotes and their heterozygote) were found at 10.6% AA, 45.6% AG and 43.8% GG in MYL2 and 60.5% AA, 34.6% AG, and 22.2% GG for ADCYAP1R1. In finished pig population, individuals containing genotype G- of MYL2 had significantly heavier carcass weight by more than 2.4 kg and thicker backfat thickness by more than 1.3 mm than those of AA homozygous pigs(p<0.05). No significant difference was found in other traits tested in this study such as marbling score, meat color, texture, moisture and separation score(p>0.05). The ADCYAP1R1 intron 2 377GG homozygotes showed coarse texture, i.e., meat quality was inferior than those of AG and AA genotypes, and the moisture level of homozygote AA was higher than those of AG and GG genotypes(p<0.05). The other carcass traits were not significantly associated with ADCYAP1R1 genotypes(p>0.05). The genetic polymorphism of MYL2 and ADCYAP1R1 genes affected the carcass traits in finished pig population. Further studies to explain the association between genetic variations and their phenotypic effects including economic traits in pigs are required including critical mutation in both genes through molecular approaches. 비육 출하돈 집단에서 MYL2 intron 5 A345G와 ADCYAP1R1 intron 2 A337G에 대한 유전자형의 분포와 도체형질과의 연관관계를 분석하였다. 조사에 이용된 두 유전자 모두 3가지 유전자형이 모두 출현하였으며, 빈도는 각각 MYL2에서 AA 10.6%, AG 45.6%, GG 43.8%, ADCYAP1R1에서 AA 60.5%, AG 34.6%, GG 22.2%로 확인되었다. MYL2 유전자형 중 G 대립인자를 보유한 돼지(-G)의 도체중과 등지방두께는 AA 동형접합자형을 보유한 도체보다 2.4kg 이상 더 무겁고, 1.3mm 이상 등지방두께가 더 두꺼운 경향을 보이고(p<0.05), 근내지방도, 육색, 조직감, 수분삼출도, 근육분리도에서는 유의차를 보이지 않았다(p>0.05). ADCYAP1R1의 유전자형 중 GG 동형접합자형인 도체에서는 조직감이 다소 떨어지는 경향을 보였으며, AA 동형접합자의 수분삼출도가 다소 높은 수준을 나타내었으나(p<0.05), 도체중, 등지방두께, 근내지방, 육색, 근육분리도에는 유의차를 보이지 않았다(p>0.05). 돼지에서 MYL2 A345G와 ADCYAP1R1 A337G의 유전자형이 비육 출하돈의 도체형질에 어느 정도 영향을 주고 있으나, 유전자의 기능에 직접적인 영향을 줄 수 있는 염기변이의 탐색 등 다양한 연구가 수반되어야 할 것으로 사료된다.